Flare changes after intravitreal injection of ocriplasmin in symptomatic vitreomacular traction syndrome - Pirani, Vittorio; Pelliccioni, Paolo; Cesari, Claudia; Carrozzi, Giulia; Cavallero, Edoardo; Mariotti, Cesare (Japanese journal of ophthalmology, 2019)
Purpose To evaluate the changes in anterior chamber flare after a single intravitreal injection of ocriplasmin (125 μg), in patients with symptomatic vitreomacular traction syndrome (VMT). Study design An institutional review board-approved single-center not randomized prospective study. Methods Fifteen eyes of fifteen patients (9 women, 6 men) underwent intravitreal injection with ocriplasmin for symptomatic VMT (width of attachment ≤ 1500 μm). Anterior segment flare was measured with a laser flare meter (Kowa) before intravitreal injection and 1 day, 1 week, 1 month after injection. The changes in flare were analyzed; the resolution of VMT was evaluated with spectral-domain OCT. Results The mean anterior chamber flare was 10.5 ± 1.9 photons per millisecond (photons/ms) before the injection. After 1 day it increased to 13.6 ± 2.7 photons/ms (p = 0.027) and after 1 week to 14.4 ± 2.5 photons/ms (p = 0.005); after 1 month it decreased to 12.3 ± 2.3 photons/ms (p = 0.123). At 1 day and 1 week after injection, mean anterior chamber flare of fellow eyes was significantly lower than study eyes, while at 1 month this difference was not significant (12.3 ± 2.3 vs. 10.5 ± 1.8 photons/ms, p = 0.124, for study and fellow eyes). There was no statistically significant difference in the changes in flare between women and men or between phakic (N = 10) and pseudophakic (N = 5) eyes. No eye demonstrated intraretinal damage at any time-point. Also, 9 eyes showed resolution of VMT while 6 eyes demonstrated persistence of VMT. Conclusion Our study shows that intravitreal injection of ocriplasmin can be a safe and effective approach to treat symptomatic VMT syndrome in selected patients.